An Investigation of the Joint Effects of Organisational Tenure and Supervisor Support on Work-Family Conflict and Turnover Intentions - Karatepe, Osman M. (Elsevier, 2009)
The purpose of this study is to investigate the interactive effects of organisational tenure and supervisor support on work-family conflict, family-work conflict, and turnover intentions. Data were gathered from a sample of Arab frontline employees married with or without children in the international five-star chain hotels in Jordan. Results of hierarchical moderated regression analysis show that the interaction of organisational tenure and supervisor support reduces family-work conflict and turnover intentions. On the contrary, this interactive term does not significantly influence work-family conflict. Implications of the aforementioned findings to alleviate family-work conflict and turnover intentions are discussed and directions for future research are offered.
Keywords: family-work conflict; hotel employees; Jordan; turnover; work-family conflict